Babao Dan induces gastric cancer cell apoptosis via regulating MAPK and NF-κB signaling pathways. Issue 10 (October 2019) - Shang, Haixia; Cao, Zhiyun; Zhao, Jinyan; Guan, Jianhua; Liu, Jianxin; Peng, Jun; Chen, Youqin; Joseph Sferra, Thomas; Sankararaman, Senthilkumar; Lin, Jiumao
Objective: The objective was to further investigate apoptosis induction by Babao Dan (BBD), which supports its anti-tumor mechanisms, using two human gastric cancer cell lines (AGS and MGC80-3). Methods: After treatment with various BBD concentrations, cell viability and cytotoxic effects were investigated using methyl thiazolyl tetrazolium (MTT) and lactate dehydrogenase (LDH) assays, respectively. The following indicators of cell apoptosis were evaluated: Annexin V-APC staining, caspase-3/-8/-9 activation, and mitochondrial membrane potential loss. Apoptosis-related protein levels (including Bcl-2-associated X protein [Bax], B-cell CLL/lymphoma 2 [Bcl-2], factor associated suicide [Fas], and Fas ligand [FasL]) were determined by western blot. The following multi-pathway factors were also assessed: p-ERK1/2, p-JNK, p-p38, and p-NF-κB. Results: The MTT and LDH assays both demonstrated increased BBD cytotoxicity. BBD induced cell apoptosis by stimulating caspase-3/-8/-9 activity and destroying the mitochondrial membrane potential. BBD also regulated key factor expression levels including Bcl-2, Bax, Fas, and FasL and down-regulated protein phosphorylation via the MAPK and NF-κB pathway. Conclusions: The possible anti-tumor mechanism is that BBD induces apoptosis via the MAPK and NF-κB signaling pathways.